Improving learning outcomes in economic activities materials through PBL models supported by interactive multimedia in sixth grade SDN Junrejo 2 - Muslikah, Amirul; Budiono; Safitri , Fita (JURNAL PENDIDIKAN DASAR NUSANTARA, 2023)
This research aimed to : (1) describe the implementation of the Problem-Based Learning (PBL) model in improving the learning outcomes of Grade VI students (2) the improvement of students' learning outcomes with the application of Problem-Based Learning (PBL) supported by interactive multimedia can enhance the learning outcomes of Grade VI students. The data collection technique used descriptive quantitative by comparing student learning outcomes after and before the class action. With data collection techniques using tests, observations, and interviews. The results of the research before the class action treatment were 8 students in the first cycle of mastery the learning outcomes of students above the KKM increased by 14 children. Whereas in cycle II the completeness of student learning outcomes increased by a total of 18 out of a total of 20 students. This can be presented before the class action classically obtained 40% then in cycle II the percentage increased to 60%. In cycle II, the percentage of completeness of student learning outcomes increased by 85%.